Ekspresi Kemarahan dalam Bahasa Melayu Pontianak Kalimantan Barat - Syarifah Lubna (tuahtalino, 2016)
Expression of anger in Pontianak Malay is the way how Pontianak Malay people in Kalimantan Barat get angry in Pontianak Malay, which are shown in furious activities, reflected in speech acts. Examples of anger expression are: beleter, ngambol, nyumpah, nyeranah, and pendek tongkeng. Béleter is talking too much, fussy, or speak without stop about the displeasure or disapproval. Beside béleter, there are other expressions of public anger in the Pontianak Malay expression which is ngambol. Ngambol is an expression of anger that are not frontal, by saying it in a tone of voice lilting and gentle but emphasize the word or sentence you wish “ambol”. It also called as ironic. Meanwhile, swearing and cursing in Pontianak in West Kalimantan Malay society known as “nyumpah” and “nyeranah”. Last but not least, expression of anger is “pendek tongkeng”. It is the silent anger expression when angry people usually only keep quiet. In Indonesian, “pendek tongkeng” commonly known as petulant or sulk also.